Accounting for Nonconvergence in Global Wool Marketing before 1939. Issue 2 (5th June 2015) - Merrett, David Tolmie; Ville, Simon
Abstract : From the mid-nineteenth century, raw wool became a global commodity as new producing countries in the Southern Hemisphere supplied the world's growing textile industries in the North. The selling practices of these big-five exporters—Australia, New Zealand, South Africa, Argentina, and Uruguay—ranged from auction through a hybrid of auction and private sale to exclusively private sale. We explore why these countries persisted with different marketing arrangements, contradicting two streams of literature on institutions: isomorphism and the new institutional economics. The article makes several important contributions through blending distinct branches of theory and by focusing on the international constraints to convergence in an earlier period of globalization.